Dual Repression by Fe(2+)-Fur and Mn(2+)-MntR of the mntH Gene, Encoding an NRAMP-Like Mn(2+) Transporter in Escherichia coli - Patzer, Silke I. (American Society for Microbiology, 2001)
The uptake of Mn(2+), a cofactor for several enzymes in Escherichia coli, is mediated by MntH, a proton-dependent metal transporter, which also recognizes Fe(2+) with lower affinity. MntH belongs to the NRAMP family of eukaryotic Fe(2+) and Mn(2+) transporters. In E. coli strains with chromosomal mntH-lacZ fusions, mntH was partially repressed by both Mn(2+) and Fe(2+). Inactivation of fur resulted in the loss of Fe(2+)-dependent repression of mntH transcription, demonstrating that Fe(2+) repression depends on the global iron regulator Fur. However, these fur mutants still showed Mn(2+)-dependent repression of mntH. The Mn(2+)-responsive transcriptional regulator of mntH was identified as the gene product of o155 (renamed MntR). mntR mutants were impaired in Mn(2+) but not Fe(2+) repression of mntH transcription. Binding of purified MntR to the mntH operator was manganese dependent. The binding region was localized by DNase I footprinting analysis and covers a nearly perfect palindrome. The Fur binding site, localized within 22 nucleotides of the mntH operator by in vivo operator titration assays, resembles the Fur-box consensus sequence.